A retrospective study of neoadjuvant novel hormonal therapy prior to radical prostatectomy for high-risk prostate cancer - Shuai, Hui; Zhang, Wei; Liu, Jianping; Zhang, Peng; Chang, Congwang; Fu, Guanghua; Wu, Tao (Frontiers in Oncology, 2025)
PurposeThis study aims to retrospectively describe the perioperative outcomes and short-term oncological outcomes of high-risk prostate cancer patients treated with neoadjuvant novel hormonal therapy (NNHT) combined with radical prostatectomy (RP) or RP alone.Materials and MethodsFifty-five male patients underwent RP and were categorized based on whether NNHT was administered preoperatively. Clinical baseline characteristics, perioperative outcomes, and biochemical recurrence (BCR) rate were summarized using mean, standard deviation, medians, interquartile ranges, and frequencies. Group 1 (n=20) received NNHT in combination with RP, while Group 2 (n=35) received RP alone. Patients in the NNHT group received androgen deprivation therapy (ADT) combined with either abiraterone (1,000 mg/d), enzalutamide (160 mg/d), or apalutamide (240 mg/d) before RP. SPSS Statistics 27 was used for statistical analysis.ResultsAmong the 55 patients included in the study, the age, clinical T stage, N stage, biopsy Gleason scores, and the number of biopsy-positive needles appeared comparable across the two groups. However, patients in the NNHT+RP group had higher median preoperative serum prostate-specific antigen (PSA) levels (39.3 ng/mL, interquartile range [IQR]: 13.9-92.3) compared to the RP-only group (15.6 ng/mL, IQR: 10.7-19.8). The NNHT+RP group showed a lower proportion of positive surgical margins (PSM) (20%) compared to the RP-only group (49%). Similarly, the proportion of patients experiencing biochemical recurrence (BCR) within the follow-up period appeared lower in the NNHT+RP group (30%) compared to the RP-only group (57%). Additionally, operative time, hemoglobin decrease, transfusion rate, catheterization time, pathological T stage, and overall complication rates showed similar distributions across the two groups.ConclusionThis study suggests that NNHT+RP may be associated with lower rates of PSM and BCR compared to RP alone. However, further studies with larger cohorts and longer follow-up are needed to assess its long-term impact on survival and other outcomes.